The Study Of Various Intention Of Swear Words Expression Reflected In The Bad Moms Movie - Wenny Pratiwi; Dwi Haryanti (Prosiding University Research Colloquium, 2020)
People communicate formally and informally based on their intention using variety ways. Using swear words is one of its variety. Varieties of swear words expression reflected in the Bad Moms movie. It is a movie which tells us the mothers’ roles. In this movie, the writers found a lot of swear words which is used by almost all the actors/actresses in this movie. The same swear words which uttered by the actors/actresses has different meaning and different use. Thus, the writer is interested in to describe the kind of utterances emerged from the use of swear word in Bad Moms movie and to describe the intention of using swear words in Bad Moms movie. The technique of data analysis was done using descriptive method in speech acts theory by Kreidler. Based on Bad Moms movie, the total of swear words uttered is 100. 16 utterances belong to the assertive utterances, 2 utterances belong to the performative, 6 swear words in verdictive utterances, 53 expressive utterances, 11 data in directive utterances, 11 in commissive utterance and 1 phatic utterance. The use of swear words in Bad Moms movie has intention to encourage the viewer to expect humor. It also used to show the relation between the actors and actresses in the Bad Moms movie.